Student teachers’ perceived changes of learning conditions during COVID-19: The role of internal resource management strategies, intrinsic motivation, and preferences for lesson formats - Paetsch, Jennifer; Schlosser, Anne (Frontiers in Psychology, 2022)
The COVID-19 pandemic caused an abrupt change in higher education that had a profound impact on students. Pandemic distance learning required students to regulate their learning more independently and find new ways of communicating with their peers and instructors. This study focus on how students perceived the learning conditions that they encountered during the first semester that took place online compare to the time before distance learning. The primary aim of this study was to investigate whether students’ internal resource management strategies, intrinsic motivation, and instruction format (synchronous, asynchronous, face-to-face) preferences were associated with the perceived changes of the learning conditions. Students enrolled in a German university (N = 330) answered an online questionnaire at the end of the summer term in 2020. Findings from structural equation modeling showed that the regulative resources of attention and intrinsic motivation were significant factors that predicted how students perceived changes in relevance, quality, and support of online instruction compare to the time before distance learning. However, our results show that these factors did not impact perceived changes in social relatedness. Moreover, the results demonstrate that preferences for digital formats were significant related to student perceptions of changes in relevance, quality, and support, whereas preferences for the face-to-face format had significant negative effects on these factors. Only the face-to-face preference had a significant (negative) effect on social relatedness. Finally, the study revealed an indirect effect of attention on students’ perceived changes of learning conditions through preferences for lesson formats. This study has important implications for digital integration in higher education and suggests that institutions should implement various methods that foster social interaction and internal regulation strategies.